Kajian Peranan Partai Politik dalam Manajemen Penetapan Anggaran Pendidikan - Agus Salim Chamidi (LPPM IAINU Kebumen, 2022)
This paper aims to determine the extent of the role of political parties in the management of budget determination, especially the budget in the education sector. This paper is qualitative by conducting a study and analysis of related laws and regulations, as well as juxtaposing them with a number of relevant scientific writings. The result shows that the position and role of political parties is very significant in the budget-setting management process.